Investigation on the Optimal Harvesting Time of Oil Palm Fruit - Arief Rahmad Maulana Akbar; Alan Dwi Wibowo; Redi Santoso (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2023)
The selection of the right timing for the harvest of oil palm fresh fruit bunch (FFB) can affect the outcome of the palm fruit quality, which can further imply the quality of crude palm oil (CPO). Truly ripen fruits can boost the yield and quality of crude palm oil. The determination of fruit ripeness is done with an approach to estimating the time of the harvest cycle and the approximate number of palm oil fruits that are detached from their bunches (loose-fruit). The study aimed to investigate the exact harvesting time with variations in the number of palm oil fruits that loose at each additional day after the occurrence of one or two fruitlets detach. The parameters used to test the quality of palm oil fruit harvested were the level of free fatty acids (FFA) and the yield of crude palm oil. The variation used was based on two factors: the number of days after the discovery of the fruit loose released from its bunch and the planting plant. The results of Analysis of Variance (ANOVA) and Duncan Multiple Range Test (DMRT) showed that the quality of oil palm fruit corresponded to the percentage of the number of palm oil fruits detached from their bunch and the age of the plant. Based on the results obtained, the optimal harvest time can be carried out until the sixth day after the first time of detached fruits for all planting ages. Keywords:   Crude palm oil, Free fatty acid, Analysis of variance test, Fruit loose, Plant age